Manajemen Berbasis Sekolah Meningkatkan Otonomi dan Akuntabilitas - Raissa Hanafiah; Syahla Iffat; Lubi Rawdhatun Nabila; Hesti Kusumaningrum (Universitas Maritim AMNI Semarang, 2025)
This article discusses the concept of School-Based Management (SBM) as an education management approach implemented in Indonesian schools. MBS aims to encourage schools to be independent, active, transparent and accountable in improving the quality of education. This article explains how SBM facilitates schools to develop education quality improvement programs according to their needs through participatory and democratic decision-making. School autonomy in decision-making results in more effective and efficient education programs, involving principals, teachers, staff, parents, students, school committees and communities. The article also discusses the importance of curriculum development and community participation in improving the quality of education in Indonesia.